2014
DOI: 10.3748/wjg.v20.i38.13734
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer arising from the remnant stomach after distal gastrectomy: A review

Abstract: Gastric stump carcinoma was initially reported by Balfore in 1922, and many reports of this disease have since been published. We herein review previous reports of gastric stump carcinoma with respect to epidemiology, carcinogenesis, Helicobacter pylori (H. pylori) infection, Epstein-Barr virus infection, clinicopathologic characteristics and endoscopic treatment. In particular, it is noteworthy that no prognostic differences are observed between gastric stump carcinoma and primary upper third gastric cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 47 publications
2
67
0
1
Order By: Relevance
“…Therefore, it remains controversial whether there is any difference in the prognosis between the malignant and benign groups. Previous studies have revealed contradictory results regarding the 5-year survival rates between initial surgery for benign disease and that for malignant disease (Table 5) [8,29,34,36,57]. No significant difference in the stage distribution was found between the two groups, except for one study; Takeda et al…”
Section: Is the Prognosis Of Rgc Different From That Of Primary Pgc?mentioning
confidence: 65%
See 1 more Smart Citation
“…Therefore, it remains controversial whether there is any difference in the prognosis between the malignant and benign groups. Previous studies have revealed contradictory results regarding the 5-year survival rates between initial surgery for benign disease and that for malignant disease (Table 5) [8,29,34,36,57]. No significant difference in the stage distribution was found between the two groups, except for one study; Takeda et al…”
Section: Is the Prognosis Of Rgc Different From That Of Primary Pgc?mentioning
confidence: 65%
“…The risk of RGC is associated with the interval after gastrectomy and the type of reconstruction. These previous studies focused on whether remnant gastric cancer had an increased risk of carcinogenesis [8]. Thereafter, the discussion moved to whether RGC has a poorer prognosis than primary proximal gastric cancer (PGC).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, chronic inflammation has been reported to occur in the stomach especially during gastric carcinogenesis involving promoter gene hypermethylation [16][17][18]. However, the epigenetic events involving carcinogenesis in the remnant stomach during the development of remnant gastric cancer have been largely unexplored [19]. We hypothesized that there would be distinct differences in DNA methylation patterns that would occur during carcinogenesis of RGC and primary gastric cancer (PGC).…”
mentioning
confidence: 97%
“…or malignant causes [9][10][11]. The incidence of gastric stump cancer reached up to 2 % in this group [12]. As in non-operated patients, atrophic gastritis, intestinal metaplasia, dysplasia, and finally gastric cancer are closely related with the H. pylori infection in PGR patients [1].…”
Section: Introductionmentioning
confidence: 99%